2005
DOI: 10.4049/jimmunol.174.11.6934
|View full text |Cite
|
Sign up to set email alerts
|

The Spermatogenic Ig Superfamily/Synaptic Cell Adhesion Molecule Mast-Cell Adhesion Molecule Promotes Interaction with Nerves

Abstract: Nerve-mast cell interaction is involved in both homeostatic and pathologic regulations. The molecules that sustain this association have not been identified. Because synaptic cell adhesion molecule (SynCAM), alternatively named spermatogenic Ig superfamily (SgIGSF), is expressed on both nerves and mast cells and because it binds homophilically, this molecule may be a candidate. To examine this possibility, mast cells with or without SgIGSF/SynCAM were cocultured with superior cervical ganglion neurons that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 50 publications
(71 reference statements)
6
112
0
1
Order By: Relevance
“…The Cadms (cell adhesion molecules) are a family of type I transmembrane proteins that have been described in several pathological and physiological processes such as the progression of lung and other cancers (reviewed in Murakami, 2005), mast cell adhesion (Ito et al, 2003(Ito et al, , 2007bFuruno et al, 2005;Ito and Oonuma, 2006), spermatogenesis (Wakayama et al, 2001;Wakayama et al, 2003;Fujita et al, 2006;van der Weyden et al, 2006;Yamada et al, 2006), epithelium development and homeostasis (Ito et al, 2007b), and central nervous system development (Biederer et al, 2002;Sara et al, 2005;Spiegel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cadms (cell adhesion molecules) are a family of type I transmembrane proteins that have been described in several pathological and physiological processes such as the progression of lung and other cancers (reviewed in Murakami, 2005), mast cell adhesion (Ito et al, 2003(Ito et al, , 2007bFuruno et al, 2005;Ito and Oonuma, 2006), spermatogenesis (Wakayama et al, 2001;Wakayama et al, 2003;Fujita et al, 2006;van der Weyden et al, 2006;Yamada et al, 2006), epithelium development and homeostasis (Ito et al, 2007b), and central nervous system development (Biederer et al, 2002;Sara et al, 2005;Spiegel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This interaction grants Cadm1 the ability to modulate the immune system by enhancing mast cell response to nerve activation (Ito et al, 2003;Furuno et al, 2005;Ito and Oonuma, 2006;Ito et al, 2007a). Another function of Cadm1 in the immune system includes immunosurveillance.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion between the neurites and mast cells was considered to be formed by specific bonds between CADM1 molecules (24,(26)(27)(28), which exist on the cell membrane of both neurites and mast cells. In addition, because the nonspecific adhesion due to electrostatic interaction would not be negligible, the contribution of the nonspecific bonds was also evaluated as F break M-S .…”
Section: Maturation Process Between the Neurites And Mast Cellsmentioning
confidence: 99%
“…In such tissues, they tend to exist near or in contact with neurites of nerve cells (20); electron microscopic observation has revealed that the intercellular distance is generally <20 nm (21,22). Many mast cells adhere to neurites when neurogenic inflammation occurs (23), and Furuno et al reported that mast cells and nerve cells bidirectionally transduce signal molecules in an adhesion-dependent manner (24,25). From these reports, the coculture system is generally regarded as a reproductive model of the anatomical and functional relationship between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation